Pushout Tests on Lightweight Composite Slabs - Chinn, James (Engineering Journal, 1965)
Tests have been performed at the University of Colorado on composite specimens using a locally produced lightweight aggregate and a commercially available headed-stud shear connector. The aggregate is an expanded shale, crushed prior to burning in a rotary kiln to produce a sealed surface. It is produced in three sizes—coarse, ľ in. to No. 4; medium, No. 4 to No. 16; and fine, No. 16 to pan. Only one mix, a six-sack mix recommended by the manufacturer, was used in tests. It weighed 93 pcf and tested in excess of 5,000 psi at 28 days when properly batched. Strengths produced in these tests, however, ranged from 3,010 to 5,818 psi. Studs used in tests were ˝, 5/8, ľ, and 7/8-in. in diameter. Lengths were roughly four times the diameter, with some variation. Tensile yield strengths ranged from 61,000 to 69,000 psi with ultimate strengths from 65,100 to 75,200 psi. Elongation in 2 in. gage length ranged from 18.5 to 25.5 percent with reductions in area from 52.8 to 66.7 percent.